Análise de desempenho da modulação GFDM em sistemas MIMO com transceptores híbridos - Silva, Edson Bezerra da (2018)
The next generation wireless communication systems require high data rates in order to satisfy the growing demands of the users. In this context, new technologies have been developed in order to comply with the requirements of mobile telephony and broadband networks, such as the proposal of new waveforms and the advancement of Multiple Input Multiple Output (MIMO) techniques. In this work we consider the Generalized Frequency Division Multiplexing (GFDM) modulation scheme, which presents advantages with regard to conventional Orthogonal Frequency Division Multiplexing (OFDM), such as the reduction of out-of-band emissions. Furthermore, we present an analysis of its performance in Hybrid MIMO Transceiver Systems (HMTS), which combine diversity and spatial multiplexing. Since previous studies have not considered the use of GFDM in hybrid scenarios, this work presents bit error rate results comparing different hybrid and diversity schemes. Based on the obtained results, this work proposes some improvements to be applied in future works, with the purpose of overcoming some of the problems detected in this study, such as high bit error rates.